Therapeutic concept and relapse prophylaxis for Achilles tendon problems in athletics - Kroesche, S. (New Studies in Athletics, 2009)
Achilles tendon problems comprise a complex of complaints that are widespread in sport, particularly among athletes in the running and jumping events. The influence of motion, the specific morphology of the Achilles tendon and the surrounding muscles, and the effects of these factors on the development of typical Achilles tendon problems are poorly understood. Such aspects are raised in sport medicine and biomechanics publications but are not always referred to in coaching publications. The purpose of this article, which is based on an extensive review of the relevant literature, is to provide a practical reference for coaches and athletes. It begins with a brief description of the biomechanics of the Achilles tendon and then covers the main problems to affect the Achilles tendon, ruptures and achillodynia, as well as the mechanisms at work in an Achilles tendon injury. It concludes with a discussion of the factors that must be taken into account by coaches and athletes in the prevention of Achilles tendon injuries: intrinsic, extrinsic, training methodological and sport medical. An accompanying article details how to plan and structure therapeutic programmes so that the athlete can return to competitive sports as soon as possible without the risk of follow-up injuries.